Influence of the product packaging towards consumer buying decision / Muhammad Farhan Mahamad Ramli - Mahamad Ramli, Muhammad Farhan (2015)
This chapter will present the overview ofthe whole research project. The purpose ofthis study is to determine the influence of the product packaging towards consumers buying decision. As today’s constantly changing marketing environment and consumer buying intention, packaging plays vital role. The main reason of packaging is to protect product, now packaging is used as a medium to sales growing and attracting potential consumers. Companies consider packaging as a medium to increase their profit and sales to reduce cost. Organizations try to influence and outline the consumer’s concept and perception through packaging.